Tear force of physically crosslinked poly(vinyl alcohol) gels with different submicrometer‐scale network structures. Issue 4 (23rd August 2014) - Noh, Taegu; Bando, Yujiro; Ota, Kensuke; Sasaki, Saori; Suzuki, Atsushi
ABSTRACT Poly(vinyl alcohol) (PVA) gels can be easily prepared by either the freeze‐thawing (FT gel) method or by the cast‐drying (CD gel) method. Although the resulting nanostructured networks of the FT and CD gels are similar, their physical properties are quite different; while CD gels are transparent and elastic, FT gels are opaque and less elastic. Moreover, the tear energy of the FT gels is much greater than that of the CD gels, which is a direct result of micrometer‐scale differences in their network structures. In order to control the distribution of microcrystallites on nano‐ and micrometer scales, FT gels were prepared from PVA solutions with different water contents. As a result, the gel gradually became more transparent as the initial water content was decreased; and accordingly, the tear energy decreased. Tear resistance was improved in the case of FT gels by repeating the number of FT cycles, whereas with CD gels, this was achieved by increasing the gelation temperature. These results indicate that the microscopic network structures are characterized by a micrometer‐scale bundled‐polymer (fibril), which determines the tear energy of FT gels. Simple methods to control the fibril network structure of FT gels using a unidirectional freezing method are presented herein, with the swelling and mechanical properties of modified FT gels discussed in terms of their multiple‐scale network structures. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41356.